Comprehensive safety assessment and therapeutic potential of Pediococcus acidilactici NMCC-B in attenuating arthritis progression - Tayyaba Zulfiqar; Muhammad Khalid Tipu; Muhammad Tariq Khan; Amr S. Abouzied; Bassam S. M. Al Kazman; Saud O. Alshammari; Qamar A. Alshammari; Abdulkarim Alshammari; Muhammad Nasir Hayat Malik; Amir Ali; Muhammad Usama Mazhar; Hafsa Jabeen (PLoS ONE, 2025)
Dysbiosis of gut microbiota and loss of gut-barrier integrity contribute to the development and severity of rheumatoid arthritis (RA). The available treatments pose a burden of major adverse effects and new treatment strategies are therefore the need of time. In this study, Pediococcus acidilactici NMCC-B (Probiotic) was evaluated for its safety and efficacy in complete Freund’s adjuvant (CFA)-induced mice model of RA. Mice were treated with either Escherichia coli (1 × 109 CFU/ml) or P. acidilactici NMCC-B (1 × 109 CFU/ml, 2 × 109 CFU/ml) to assess acute, sub-acute, and chronic toxicities. In RA model, mice were either pre-treated with daily dose of P. acidilactici NMCC-B or treated concurrently (day 1–day 27) or post-treated (day 28–day 42). P. acidilactici NMCC-B inhibited gut permeability, lessened joint inflammation, and ameliorated RA progression. No signs of toxicity, pathogenicity or bacterial translocation were observed in animals treated with probiotic. P. acidilactici NMCC-B also restored total body weight, attenuated inflammation, improved antioxidants, alleviated soft tissue swelling, bone damage, and the expression of IL-1β, NF-κB and TNF-α in paw tissue. Based on current findings, it is perceivable that P. acidilactici NMCC-B could be a promising candidate for the management of RA.